The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/polym13020214
|View full text |Cite
|
Sign up to set email alerts
|

Role of pKA in Charge Regulation and Conformation of Various Peptide Sequences

Abstract: Peptides containing amino acids with ionisable side chains represent a typical example of weak ampholytes, that is, molecules with multiple titratable acid and base groups, which generally exhibit charge regulating properties upon changes in pH. Charged groups on an ampholyte interact electrostatically with each other, and their interaction is coupled to conformation of the (macro)molecule, resulting in a complex feedback loop. Their charge-regulating properties are primarily determined by the pKA of individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 67 publications
(47 reference statements)
2
41
0
Order By: Relevance
“…As a result the net charge of the monomer is negative. As discussed in ref , the net charge of such a polyampholyte block should be almost indistinguishable from that of a polyacid block with the same p K A .…”
Section: Simulation Model and Methodsmentioning
confidence: 87%
“…As a result the net charge of the monomer is negative. As discussed in ref , the net charge of such a polyampholyte block should be almost indistinguishable from that of a polyacid block with the same p K A .…”
Section: Simulation Model and Methodsmentioning
confidence: 87%
“…This last simplification was validated a posteriori by agreement between the trends observed in simulations and in experiments, suggesting that the neglected interactions are not dominant in the studied system. Similar coarse-grained models are ubiquitous in polymer science and have been used in our previous publications to model short peptides 29,30 or disordered proteins. 31 The simulation box length was chosen such that one hyperbranched polymer in the simulation box corresponds to cglyc = 1.5 mg/mL, assuming that one bead corresponds to one glucose unit of glycogen.…”
Section: Theoretical Modelmentioning
confidence: 97%
“…Srivastava and co-authors demonstrated that the charge regulation mechanism is the most important contributor in protein-polyelectrolyte complexation regardless of pH and other physical chemistry parameters using constant-pH Monte-Carlo simulations [ 71 ]. In addition, it has also been recently shown that the presence of “charged patches” along the polyelectrolyte is also an important factor in the stability of the protein/peptide interactions [ 72 , 73 ].…”
Section: Current Approaches To the Design Of Interfacial Peptidesmentioning
confidence: 99%